Influence of online consumer reviews on brand choice - LUI, Patricia (Institutional Knowledge at Singapore Management University, 2018)
Social interaction encourages consumers toshare information in the digital age. Many consumers use online reviews of products and services to supporttheir brand choice. The concept ofreference group explains how peers can influence consumer purchasedecisions. Peers can exert influence onconsumers in the forms of informational, utilitarian and value-expressiveinfluences. This proposed study aims atexamining how these three forms of reference group influence would affectconsumers in using online consumer reviews when making a brand choice decision. It also explores the role of brand trust onthe brand choice. This paper serves thepurpose of providing a conceptual framework for developing further research.